Inside the belly of the beast. Reflections on the history of IRCT - Christian Pross (Torture)
This paper is looking back and taking stock of the history of IRCT from the perspective of a founder of a treatment centre, former member of the IRCT council and ExCom and author of Torture Journal. It is the story of enthusiasm, ambition, dedication, devotion, hope and dreams that the worldwide battle against torture could be won in the near future. And it is also the story of a rocky road with failures, disillusionment, disappointment, team conflicts and burnout which commonly but insufficiently is described as “vicarious traumatization”. Most centres were established by charismatic, visionary pioneers with entrepreneurial skills and a missionary sense, which enabled them to build and defend their organisations against reluctant bureaucracies and the prevailing attitude of denial and indifference in society. Because they tended to ignore and neglect structural issues and develop a sense of grandiosity, these types of leaders often obstructed the transformation of the organisation into a professionally managed health care institution.